Predicting Sugar Balance as the Impact of Land-Use/Land-Cover Change Dynamics in a Sugarcane Producing Regency in East Java, Indonesia - Artikanur, Salis Deris; Widiatmaka, Widiatmaka; Setiawan, Yudi; Marimin, Marimin (Frontiers in Environmental Science, 2022)
Lamongan Regency is one of Indonesia’s regencies in Indonesia that contribute to the country’s sugarcane and sugar production. Land-use/land-cover changes (LULC) have happened in various areas, including Lamongan Regency in East Java, Indonesia. This study aimed to analyze the impact of land-use/land-cover change (LULCC) in 2007–2031 on the sugar balance in the Lamongan Regency in 2031. The LULC forecast in 2031 was made using R studio using the CLUE-s function in the LULCC package. Following that, the sugar requirements and sugar balance in Lamongan Regency in 2031 were forecasts. The kappa accuracy of the LULC model tested in 2019 was 0.81 when using the CLUE-s model in R studio’s LULCC package. The findings of the LULC prediction in Lamongan Regency for 2031 indicated that there could be significant changes in LULC, resulting in an estimated reduction in 1,687.5 ha sugarcane, influenced by LULC competition for built-up areas. The Built-up areas in Lamongan Regency have exploded in size as a result of population. An increase in built-up areas and a reduction in sugarcane plantations as a result of LULCC are expected to diminish the sugar balance in Lamongan Regency by 10,470.76 tons in 2031 when compared to 2019. The results of this study can be utilized to prevent uncontrolled LULCC in the future to meet sugar needs in Lamongan Regency and at the national level.